Spanish Pre-Olympic Athletes’ Motivations and Barriers to Pursuing Dual Career as a Function of Sociodemographic, Sport and Academic Variables - Mateo-Orcajada, Adrián; Leiva-Arcas, Alejandro; Vaquero-Cristóbal, Raquel; Abenza-Cano, Lucía; García-Roca, Juan Alfonso; Meroño, Lourdes; Isidori, Emanuele; Sánchez-Pato, Antonio (Frontiers in Psychology, 2022)
The dual career allows elite athletes to attain their maximum competitive and academic performance, but the COVID-19 pandemic hindered their development and changed their perception of the importance given to the sporting and educational environment. For this reason, the aim of the present study was to determine the differences in the motivations and perceived barriers, the importance given to academic qualifications, and the perception of the dual career from a multifactorial perspective, of elite athletes according to sex, type of sport practiced, job performance, time of sports career, type of athlete, and type of scholarship received. A total of 100 student-athletes participated in the research study by completing the "Perceptions of dual career student-athletes" questionnaire. The results showed that athletes from individual modalities (p=0.012) and those who did not receive any scholarships described more barriers (p<0.001). In addition, women studied more because they enjoyed it (p=0.007); athletes from individual modalities studied to work later (p=0.008); athletes who do not work perceived a greater influence between study and sports performance (p=0. 029); at the beginning and at the best stage of their sports career, a greater influence of academics on performance was perceived (p=0.016); and athletes who considered themselves professionals, and athletes who did not receive any scholarships (p=0.025), reported that the conciliation between sports and academic life was difficult (p=0.034). The results obtained point to the importance of dual career scholarships for student-athletes, as well as the need for the programs implemented for these athletes to consider sex, sport modality or type of scholarship granted.